Respostas
respondido por:
3
x² + 6x + 9 = 49
x² + 6x + 9 - 49 = 0
x² + 6x - 40 = 0
a = 1
b = 6
c = - 40
Δ = b² - 4.a.c
Δ = 6² - 4. 1 . ( - 40)
Δ = 36 + 160
Δ = 196
x = - b + - √Δ/2a
x = - 6 + - √196/2.1
x = - 6 + - 14/2
x' = 8/2 ⇒ x' = 4
x" = - 20/2 ⇒ x" = - 10
S = { 4 e - 10 }
x² + 6x + 9 - 49 = 0
x² + 6x - 40 = 0
a = 1
b = 6
c = - 40
Δ = b² - 4.a.c
Δ = 6² - 4. 1 . ( - 40)
Δ = 36 + 160
Δ = 196
x = - b + - √Δ/2a
x = - 6 + - √196/2.1
x = - 6 + - 14/2
x' = 8/2 ⇒ x' = 4
x" = - 20/2 ⇒ x" = - 10
S = { 4 e - 10 }
daisycastro:
Obrigado por marcar como a melhor resposta!!!!
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás